This I Believe - Bartlett, Florence Dibell (Tufts Archival Research Center, 2006)
Florence Bartlett describes how her belief in the unity of humanity developed during an encounter with Bedouins in the Sahara desert, and explains her decision to create a museum of folk art, which expresses that bond of unity between peoples.